Results of Kansas demonstrations on implanting suckling calves and yearlings - Corah, L.; Schwartz, F.; Brazle, F.; Orwig, T.; Francis, G. (Kansas State University. Agricultural Experiment Station, 2011)
To encourage greater use of implants in beef cattle industry in Kansas, 62 implant demonstrations were conducted in 31 different counties in Kansas. 1,402 implanted suckling calves gained an average of 15.1 pounds more than 694 non-implanted calves. In 19 yearling trials, 616 implanted yearling steers and heifers gained 20.0 pounds more than 365 yearlings. The results suggest utilizing implants as a regular management practice for suckling steer calves and yearling steers and heifers.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Implants; Calves; Yearlings